Improving the performance of carbon/graphite composites through the synergistic effect of electrostatic self-assembled carbon nanotubes and nano carbon black. Issue 24 (15th December 2022) - Li, Jie; Li, Hao; Gao, Guoqiang; Yang, Zefeng; Lin, Jiahui; Huang, Xuefei; Zhao, Yang; Chen, Qichen; Wei, Wenfu; Wu, Guangning
Abstract: Superior performance fillers are considered as an effective means to enhance the performance of carbon/graphite composites. However, poor interfacial properties and incomplete filler networks limit the performance enhancement of the composites. In this study, a new method was proposed to weaken this impact through the synergistic effect of the electrostatic self-assembly of nano carbon black (NCB) onto carbon nanotubes (CNTs). The results showed that the synergistic effect between NCB and the CNTs significantly improved the mechanical and electrical properties of the composites. NCB reduces the porosity of the composites and increases the interaction between the CNTs and matrix. The compressive strength of the composite was 143.2 Mpa, and the flexural strength was 46.3 MPa, which is 210% higher than that of the pristine carbon/graphite composites. Moreover, NCB and CNTs form a globally connected synergistic network in the carbon skeleton. Composites filled with CNTs/NCB exhibited the lowest resistivity and highest thermal conductivity, with a resistance that was 42% lower than that of pristine carbon/graphite composites at 44.8 μΩ m. All of these results suggest that the synergistic effect of CNTs/NCB show great potential to improve the performance of carbon/graphite composites. Graphical abstract: Image 1 Highlights: NCB was self-assembled with CNTs by electrostatic force, forming an enhanced phase with synergistic effect. Targeted improvement of matrix properties near CNTs using NCB can enhance the interfacial properties. Self-assembly of CNTs with NCB forms a synergistic network in the composite to enhance electrical and thermal properties.